EFEK KETERAMPILAN SOSIAL DAN JOB CRAFTING TERHADAP KETERIKATAN KERJA - Robbaanii, Mega Maghfira; Baihaqi, MIF; Juwitaningrum, Ita (Program Studi Psikologi Universitas Pendidikan Indonesia, 2019)
When a company has employees with high keterikatan kerja, the company will have employees who are able to carry out and modify work according to their capabilities. The other hand, job crafting plays an important role in change management and organizational success, this is because employees will be able to overcome problems in the workplace by modifying work according to their capabilities. Job crafting is directly and positively influenced by keterampilan sosials to interact effectively and influence others in the workplace. This study used linear regression that participated by 53 employees. The results were keterampilan sosials and job crafting had an effect on keterikatan kerja on employees by variance explained of 46.1 percent.